2005
DOI: 10.1177/1077801205278042
|View full text |Cite
|
Sign up to set email alerts
|

Children in the Crossfire

Abstract: Although most states mandate considerations of intimate partner violence (IPV) in child custody proceedings, little is known about how often a preexisting history of IPV is effectively presented to the courts in dissolution cases and, when it is, what effect it has on child custody and visitation outcomes. This retrospective cohort study examined the effects of a history of IPV, further categorized by whether substantiation of that history existed and whether the court handling the custody proceedings knew of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Family courts determine physical and legal custody of children, parenting time arrangements, and thus, abusers’ level of court ordered access to women and their children after the relationships end (Hardesty & Ganong, 2006; Kernic et al, 2005). Mediation is a widely used process to negotiate child custody among divorcing couples.…”
Section: Family Court’s Role In Determining Abusers’ Access To Mothermentioning
confidence: 99%
See 2 more Smart Citations
“…Family courts determine physical and legal custody of children, parenting time arrangements, and thus, abusers’ level of court ordered access to women and their children after the relationships end (Hardesty & Ganong, 2006; Kernic et al, 2005). Mediation is a widely used process to negotiate child custody among divorcing couples.…”
Section: Family Court’s Role In Determining Abusers’ Access To Mothermentioning
confidence: 99%
“…Previous research on the custody negotiation process has primarily relied on quantitative or archival data (Johnson et al, 2005; Kernic et al, 2005; Rosen & O’Sullivan, 2005); therefore the current mixed-method study was designed to elicit, in women’s own words, whether they shared their safety concerns during mediation, how they were treated throughout the mediation process, and how this treatment affected their view of the system and willingness to reuse the system if necessary.…”
Section: Abused Women’s Treatment In Family Courtmentioning
confidence: 99%
See 1 more Smart Citation
“…Women report that abusers continue to use their children to exert control over them by threatening the children’s lives, mistreating their children to punish mothers, and being physically abusive towards the children (Hardesty & Ganong, 2006; Slote et al, 2005). Mothers have also mentioned difficulties in getting their children back from visitations or, in instances where the mother is the noncustodial parent, having the abusive fathers restrict their access to the children (Bemiller, 2008; Hardesty & Ganong, 2006; Kernic, Monary-Ernsdorff, Koepsell, & Holt, 2005). On the extreme end, post-separation abuse (PSA) results in fathers kidnapping or murdering mothers and/or children (Jaffe et al, 2003; Saunders, 2009).…”
Section: Post-separation Abusementioning
confidence: 99%
“…Custody evaluators in a small, nonrandom survey (primarily psychologists in independent practice) indicated that in half of cases with a single IPV perpetrator, evaluators recommended the victim receive sole legal and physical custody; however, in 39% of cases they recommended joint legal custody, with primary physical custody recommended for the victim (Bow & Boxer, 2003). ' Raising further concems, several representative studies involving record reviews or survivor interviews showed little or no difference in custody and visitation outcomes for cases with and without IPV (Kemic, Monary-Emsdorff, Koepsell, & Holt, 2005;Logan, Walker, Jordan, & Horvath, 2002;O'Sullivan, 2000;O'Sullivan, King, Levin-Russell, & Horowitz, 2006). Some researchers have focused on the weight evaluators give to family violence.…”
mentioning
confidence: 96%